2014
DOI: 10.1007/s11418-014-0847-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Glycyrrhiza uralensis Fisch. ex DC. containing high concentrations of glycyrrhizin by Eastern blotting and enzyme-linked immunosorbent assay using anti-glycyrrhizin monoclonal antibody for selective breeding of licorice

Abstract: A rapid selection system was used to screen Glycyrrhiza uralensis plants containing high concentrations of glycyrrhizin (GC) by Eastern blotting using anti-GC monoclonal antibody (MAb). Chromatographic fingerprinting by Eastern blotting correlated with the GC concentration analyzed by enzyme-linked immunosorbent assay (ELISA). The roots of wild G. uralensis growing in Mongolia were analyzed by Eastern blotting to identify plants containing high concentrations of GC, and the GC concentration was confirmed by EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Consequently, licorice is known as “the king of herbs” or “Guo lao” in Chinese, meaning “national venerable master” . It appears in approximately 60% of TCM prescriptions and 70% of herbal formulas in Japan . In TCM, licorice is usually processed with honey and traditionally used as a decoction , which is considered to change the property of licorice from cool to warm .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, licorice is known as “the king of herbs” or “Guo lao” in Chinese, meaning “national venerable master” . It appears in approximately 60% of TCM prescriptions and 70% of herbal formulas in Japan . In TCM, licorice is usually processed with honey and traditionally used as a decoction , which is considered to change the property of licorice from cool to warm .…”
Section: Introductionmentioning
confidence: 99%
“…MAb 3A3 we used in this assay was an IgG antibody with a k‐type light chain and showed low cross‐reactivities against the structurally related compounds found in Taxus species, which ensured its high specificity to Tax. Given the rather low Tax content in the shoot bark of Taxus (the highest level being only 0.022% in Taxus samples, as shown in Table ), a highly sensitive and specific assay system is essential for the breeding of medicinal plants like Glycyrrhiza species previously succeeded by us using ELISA (Fujii et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Licorice is also widely used as a sweetener in the production of confectioneries, soy sauce and is therefore in high demand worldwide. An anti-GC MAb was prepared in our laboratory [14] and we previously reported on the synergistic effects of GC and other constituents [37], the interfacial behavior of GC [77], and the identification of Glycyrrhiza species with higher GC content [27]. More recently we found that two flavonoids, isoliquiritigenin and formononetin promote in vitro fertilization [78].…”
Section: Licoricementioning
confidence: 99%
“…We prepared many MAbs against natural products like forskolin [1], solamargine [2], crocin [3], marihuana compound [4], opium alkaloids [5], ginsenosides [6,7], berberine [8], sennosides [9,10], paeoniflorin [11,12], glycyrrhizin (GC) [13,14], saikosaponin [15][16][17], ginkgolic acid [18], aconitine alkaloid [19] and baicalin [20]. More recently MAbs against capsaicinoids [21], artemisinin [22,23], luteoloside [24], daidzin [25] and puerarin [26] have been prepared and developed individual competitive enzyme-linked immunosorbent assay (ELISA) as a high sensitive, specific, and simple methodology resulting in screening of medicinal plants targeting bioactive component [27], pharmacokinetics for capsaicinoids [21] artemisinin [28], and ginsenoside Rb1 and Rg1 [29].…”
Section: Introductionmentioning
confidence: 99%